Pengaruh Promosi dan Demosi Terhadap Prestasi Kerja Karyawan Pada PT Wira Eka Persadatama - Anugrah Ilahi, Andi Alfianto (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2021)
This research aims to find out the effect of promotion and demotion on employee performance on PT. Wira Eka Persadatama Parepare. The analytical method used in this study is the quantitative analysis method which is a method of multiple linear regression analysis. The results of this study showed that partially the promotion variable (X1) was positive for employee work performance (Y) because the > t table (3,026 > 2,018) meant that Ho was rejected, indicating a significant promotion to employee work performance at PT. Wira Eka Persadatama Parepare, while partially the demotion variable (X2) does not have a positive effect on employee work performance (Y) because the calculation of < t table (0.117 < 2.018) means ho is accepted, this shows that demotion does not have a considerable influence on employee work performance at PT. Wira Eka Persadatama Parepare. Promotion variables (X₁) and work demotion (X₂) simultaneously have a negating effect on employee work performance because F calculates the > F table where the value is (5,313 > 3.20) then Ho is rejected and Ha is accepted. It also means the influence between independent variables on a dependent variable.